STABILITAS REAKSI ENZIMATIK KADAR TRIGLISERIDA SERUM METODE Glyserol Phosphate Oxidase Para-Aminoantipyrin (GPO-PAP) DENGAN VARIASI WAKTU INKUBASI - Endrique Putri, Salmanda; Kurnaeni, Nani; Nurhayati, Dewi; Merdekawati, Fusvita (Jurnal Kesehatan Siliwangi, 2024)
One of the triglycerides test lipid profile examination that is often analyzed because it provides information about cardiovascular health and stroke. Laboratory services have an important meaning in making a diagnosis based on the patient's health history and are an integral part in achieving quality laboratory results that have accurate accuracy and precision. Analytical factors that can influence examination results include incubation time. The delay in the length of incubation time is due to the limited number of laboratory personnel and inadequate equipment. The objective of this study was to assess the impact of stability on serum triglyceride levels using the GPO-PAP method with different incubation durations. The research employed a quasi-experimental design, utilizing serum samples from three Medical Laboratory Technology students. The samples were subjected to varying incubation times of 10, 60, 75, 90, and 105 minutes at room temperature, with each condition being repeated five times. The mean results of serum triglyceride levels with incubation times of 10, 60, 75, 90, and 105 minutes respectively were 80,0 mg/dL, 79,00 mg/dL, 76.36 mg/dL, 73.65 mg/ dL, and 67.94 mg/dL. Data analysis was conducted using the General Linear Model (GLM) test, with significance indicated by the Sig value. < 0.05 means that triglyceride levels with an incubation time of 75 minutes are statistically unstable.